2018
DOI: 10.5152/tjar.2017.88965
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Procalcitonin for Differentiating Bacteraemic Gram-Negative Sepsis from Gram-Positive Sepsis

Abstract: Patients with gram-negative sepsis had higher PCT values than those with gram-positive sepsis. Our results suggest that PCT value may be a useful tool for distinguishing between gram-negative and gram-positive bacteraemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…In our study, PCT in the CPSS group was significantly higher than that in the CNSS group. Several studies have indicated that PCT levels are significantly higher in adult patients with gram-negative sepsis than in adult patients with gram-positive sepsis (25)(26)(27)(28). However, in this study, subgroup analysis showed that there was no significant difference in PCT levels between gram-positive and gram-negative septic shock in children.…”
Section: Discussioncontrasting
confidence: 85%
“…In our study, PCT in the CPSS group was significantly higher than that in the CNSS group. Several studies have indicated that PCT levels are significantly higher in adult patients with gram-negative sepsis than in adult patients with gram-positive sepsis (25)(26)(27)(28). However, in this study, subgroup analysis showed that there was no significant difference in PCT levels between gram-positive and gram-negative septic shock in children.…”
Section: Discussioncontrasting
confidence: 85%
“…The statistical analysis of PCT levels on the first day of microbiological identification in blood samples in this sample of extensively burned patients confirmed previous reports demonstrating significantly higher values in the presence of Gram-negative bacteria comparing with controls or patients with Gram-positive sepsis. [10][11][12][13] The difference was most pronounced when causative agents were glucose nonfermenting bacilli, particularly Acinetobacter and Pseudomonas spp., or Enterobacteriaceae rods, like E. coli or K. pneumoniae. On the other hand, a statistical difference in PCT levels was not found between in PCT levels of patients with sepsis caused by Gram-positive bacteria and control patients, with the exception of patients with sepsis caused by Streptococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Kan kültürü üremesi için PCT eşik değeri 3.29 olarak belirlendi ve PCT'nin bakteriyemiyi ayırt etme yeteneğinin orta düzeyde olduğu (%70-%80) tespit edildi. Eş zamanlı antibiyotik kullanımı, yavaş üreyen veya kültürde üremeye uygun olmayan patojenlerin varlığı gibi nedenlerle sepsis hastalarının %30'unda kan kültürünün negatif olarak sonuçlanabileceği bildirilmiştir (6). Çalışmamızda da PCT değeri çok yüksek olduğu halde kan kültürlerinde üreme olmayan hastalar mevcuttu.…”
Section: Bulgularunclassified